HDAC4 and HDAC5 form a complex with DREAM that epigenetically down-regulates NCX3 gene and its pharmacological inhibition reduces neuronal stroke damage. Issue 10 (October 2020) - Formisano, Luigi; Laudati, Giusy; Guida, Natascia; Mascolo, Luigi; Serani, Angelo; Cuomo, Ornella; Cantile, Maria; Boscia, Francesca; Molinaro, Pasquale; Anzilotti, Serenella; Pizzorusso, Vincenzo; Di Renzo, Gianfranco; et al.
The histone deacetylases (HDACs)-dependent mechanisms regulating gene transcription of the Na + /Ca + exchanger isoform 3 ( ncx3 ) after stroke are still unknown. Overexpression or knocking-down of HDAC4/HDAC5 down-regulates or increases, respectively, NCX3 mRNA and protein. Likewise, MC1568 (class IIa HDACs inhibitor), but not MS-275 (class I HDACs inhibitor) increased NCX3 promoter activity, gene and protein expression. Furthermore, HDAC4 and HDAC5 physically interacted with the transcription factor downstream regulatory element antagonist modulator (DREAM). As MC1568, DREAM knocking-down prevented HDAC4 and HDAC5 recruitment to the ncx3 promoter. Importantly, DREAM, HDAC4, and HDAC5 recruitment to the ncx3 gene was increased in the temporoparietal cortex of rats subjected to transient middle cerebral artery occlusion (tMCAO), with a consequent histone-deacetylation of ncx3 promoter. Conversely, the tMCAO-induced NCX3 reduction was prevented by intracerebroventricular injection of siDREAM, siHDAC4, and siHDAC5. Notably, MC1568 prevented oxygen glucose deprivation plus reoxygenation and tMCAO-induced neuronal damage, whereas its neuroprotective effect was abolished by ncx3 knockdown. Collectively, we found that: (1) DREAM/HDAC4/HDAC5 complex epigenetically down-regulates ncx3 gene transcription after stroke, and (2) pharmacological inhibition of class IIa HDACs reduces stroke-induced neurodetrimental effects.